Microstructure evolution of the rapidly solidified alloy powders and composite powders. (15th November 2019) - Yang, Q.; Liu, Y.T.; Liu, J.; Wang, L.; Chen, Z.; Wang, M.L.; Zhong, S.Y.; Wu, Y.; Wang, H.W.
Abstract: In the present work, the size-dependent microstructure evolution of the Al-Zn-Mg-Cu alloy powders and the TiB2 /Al-Zn-Mg-Cu composite powders are studied experimentally and theoretically. Several different types of microstructures are formed within alloy powders as a function of powder size but just one type is formed within the composite powders. The transitions in microstructure within a powder such as planar interface breaking down into cellular microstructure are also observed. The occurrence of the planar interface is analyzed in terms of critical undercooling and critical cooling rate, and the breaking down of planar interface is correlated with the thermal history of the droplets modeled by Newtonian thermokinetics and interface velocity modeled by BCT models. In the composite powders, the location of TiB2 particles depends on the entrapment/pushing by the solid/liquid interface. The disturbance of temperature field and multiple nucleation sites due to the introduction of TiB2 particles contribute to the variation in the microstructure of alloy powders and composite powders. Graphical abstract: Unlabelled Image Highlights: Featureless, cellular/dendrite microstructures are formed within the alloy powders. The microstructure evolutions and transitions depend on the thermal history of the droplet. The breaking down of planar interface is discussed from critical undercooling, cooling rate and interface velocity. The non-planar solid/liquid interface and lower undercooling make the discrepancy of the location of nanoparticles. The temperature disturbance and multiple nucleation events lead to equiaxed microstructure in the composite powders.